THE EFFECT OF MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK SATISFACTION AS INTERVENING (CASE STUDY IN THE TECHNICAL DEPARTMENT OF PT SEMEN PADANG) - ., Rusman Hidayat; Heryanto (Archives of Business Research, 2019)
This study aims to determine the effect of motivation, compensation and job satisfaction on employee performance. The population in this study amounted to 285 employees and a sample of 167 respondents. This research was conducted in the Engineering Department, PT. Semen Padang by using primary data obtained through questionnaires. The data analysis technique used is Path Analysis technique and is operated through SPSS 16.0. The results showed that motivation had a significant effect on job satisfaction, compensation had a significant effect on job satisfaction, job satisfaction had a significant effect on employee performance, motivation and compensation directly had a significant effect on employee performance, motivation through job satisfaction had a significant effect on employee performance, compensation through satisfaction work on performance has no significant effect.